Exploring Internal and Environmental Moderators of Entrepreneurial Orientation - Performance Relationship in Bulgarian Enterprises - Davidkov, Tsvetan; Yordanova, Desislava I. (International Review of Management and Marketing, 2017)
Moderators of entrepreneurial orientation – performance relationship have not been sufficiently examined in the existing literature especially in countries operating in Central and Eastern Europe. The purpose of the present study is to explore internal and environmental moderators on entrepreneurial orientation – performance relationship in a sample of Bulgarian enterprises. The relationship between entrepreneurial orientation and firm performance is stronger when the chief executive officer has no ownership stake in the company. Environmental dynamism and access to financial resources are not able to moderate the entrepreneurial orientation – performance relationship. These findings indicate that the moderating effects of environmental dynamism and access to resources identified in previous empirical studies may not be universal across all countries and contexts. The paper comments practical implications of the findings and recommendations for future research. Keywords: entrepreneurial orientation, performance, mediating effects, Bulgaria. JEL Classification: M19